2020
DOI: 10.1186/s13075-020-02229-5
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 receptor blockade or TNFα inhibition for reducing glycaemia in patients with RA and diabetes: post hoc analyses of three randomised, controlled trials

Abstract: Background Diabetes is common in patients with rheumatoid arthritis (RA). Interleukin (IL)-6 is implicated in both the pathogenesis of RA and in glucose homeostasis; this post hoc analysis investigated the effects of IL-6 receptor vs. tumour necrosis factor inhibition on glycosylated haemoglobin (HbA1c) in patients with RA with or without diabetes. Methods Data were from two placebo-controlled phase III studies of subcutaneous sarilumab 150/200 mg q2w + methotrexate or conventional synthetic disease-modifyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 54 publications
1
18
0
1
Order By: Relevance
“…The current study's findings revealed that serum cytokine IL-6 level were significantly higher in diabetic group 82.24% p < 0.001 in compared to control group. These findings are consistent with Genovese, et al [17] who stated that high levels of IL-6 are a risk factor for T2D and that IL-6 alone or in combination with IL-1β, impairs β cell activity. Furthermore, IL-15 and IL-6 could be employed as biomarkers for the development risk of autoimmune diabetes Siewko, et al [18].…”
Section: Animals and Experimental Design: Thirty Malesupporting
confidence: 92%
“…The current study's findings revealed that serum cytokine IL-6 level were significantly higher in diabetic group 82.24% p < 0.001 in compared to control group. These findings are consistent with Genovese, et al [17] who stated that high levels of IL-6 are a risk factor for T2D and that IL-6 alone or in combination with IL-1β, impairs β cell activity. Furthermore, IL-15 and IL-6 could be employed as biomarkers for the development risk of autoimmune diabetes Siewko, et al [18].…”
Section: Animals and Experimental Design: Thirty Malesupporting
confidence: 92%
“… 140 Consistent results were observed with SAR in a posthoc analysis, where SAR was associated with a greater reduction in glycosylated haemoglobin (HbA1c) than placebo or ADA in patients with diabetes. 141 …”
Section: Resultsmentioning
confidence: 99%
“…results were observed with SAR in a posthoc analysis, where was associated with a greater reduction in glycosylated haemoglobin (HbA1c) than placebo or ADA in patients with diabetes. 141 Safety analyses of TCZ on haematological variables found significant increases in haemoglobin and haematocrit levels in anaemic and non-anaemic patients with RA compared with other biological and non-biological DMARDs. By contrast, TCZ-treated patients had higher rates of grade 1/2 or 3/4 neutropenia than placebo; however, neutropenia was not associated with serious infections and improved after dose reduction or discontinuation of TCZ.…”
Section: Vaccinationmentioning
confidence: 98%
“…In particular, simultaneous blockade of IL-4Ra, a common part of the receptor complex of IL-4 and IL-13, with Dupilumab showed significant therapeutic effect and is approved for patients with severe eosinophilic asthma [ 8 , 9 ], despite poor efficacy of single anti-IL-4 and anti-IL-13 therapeutics [ 58 , 59 , 60 , 61 ]. Under inflammatory conditions TNF and IL-6 demonstrate some functional redundancy: for example, they both mediate inflammatory response during sepsis [ 62 ], and may act as immunometabolic transmitters [ 63 , 64 , 65 ]. On the other hand, due to distinct intracellular signaling of their cognate receptors, these cytokines may exhibit distinct functions or work synergistically to promote inflammation [ 66 , 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%